Antimicrobial Susceptibility Pattern of Uropathogenic Bacteria in RMMC Hospital of Chidambaram - Gnanasekaran, A.; Manikandan, P.; Vigneshwari, J.; Poongothai, P.; Senthilkumar, P. K. (Journal of Drug Delivery and Therapeutics, 2019)
Background: In every year millions of people were affected by the Urinary Tract Infection. It was creating a serious health issue. Aim: The present study was to analysis of the uropathogenic bacteria in patients were attended RMMC Hospital and their antibiotic resistance pattern, in vitro detection of haemolysis virulent factor of uropathogenic. Material and Methods: All urine samples were tested by the standard microbiological procedure. Kirby-Bauer method used for the Antibiotic Susceptibility Test according to the CLSI guidelines. Commercially available antibiotics were used. Blood Agar used for the detection of haemolysis. Results: A total of 261 urine samples were included in this study. We isolated a total of 103 positive cultures. 12% of Gram-positive, 83% of Gram-negative bacteria and 3% of Candida fungi. Escherichia coli was the most predominant bacteria (54%) followed by Klebsiella sp (15%), Staphylococcus aureus (12%), Pseudomonas aeruginosa (12%), Proteus (1%) and fungi Candida (3%). Mostly female patients’ sample were analysed and the inpatient higher majority than the outpatients. Conclusion: Escherichia coli are the common bacteria to cause of UTI. Nowadays most of the uropathogens are to resistance to the overall antibiotics. This kind of reactions creating the life-threatening of humans. Keywords: Antibiotic, Antibiotic Susceptibility Test, Uropathogens, Resistance, Haemolysis